STORY TELLING TO INCREASE ENGLISH SPEAKING ABILITY AT TENTH GRADE STUDENTS OF SMK PGRI 2 KEDIRI - Nur Kholimah D.N; Dewi Kencanawati; Yunik Susanti (Media Inovasi Pendidikan dan Publikasi, 2024)
Speaking ability is an interactive process of building meaning that involves the production and reception and processing of information. Meanwhile, speaking ability is expressing feelings,ideas, opinions, to other people by using the articulation of words or sounds to provide information. Mastering speaking skills is a top priority that students must have, but there are still many students who face difficulties speaking English, start from difficulties expressing vocabulary, accuracy, fluency, coherence, spelling pronouns in English. The purpose of the research is: 1).To know students' speaking ability to Speak English before being taught by using Storytelling of Tenth Grade at SMK PGRI 2 Kediri. 2.) To know students' speaking ability to Speak English After being taught by using Storytelling to increase speaking ability to the students SMK PGRI 2 Kediri. 3.) To find out whether there is any impact or not using Storytelling to Increase English Speaking Ability at SMK PGRI 2 Kediri. This research was carried out in October-November 2023. The population of this research was class 10 student at SMK PGRI 2 Kediri, and each class was 28 students. This research was carried out in eight meetings which include Pre-test, Treatment and Post-test. Researcher use (speaking orally) as a instrument to collect the data. The researcher was carried out from September 2023 until December 2023. After collecting the datamteh next step was to analyzed the data using SPSS vs 24.0,specifically using the t-test sample to determine the significant influence of habituation storytelling on students speaking abilites. The research result showed that students speaking skills improved after being taught using storytelling method. This is proven by the average scores in 2 classes (control class and experiment class). The result shows that the control class that are not given the treatment get the score pre-test 43.2 and posttest 53.0 score got higher than t-table (2.767>2.473) and in experiment class are given the treatment get the score pretest 40.3 and posttest 75.7. The result report that the t-test was higher that t-table (11.420>2.473).It means Ho was rejected and Ha was accepted. The researcher suggest to the English teacher that will better teach the students using habituation storytelling because it was suitable technique which makes the student easier to understand speak clearly.